OSOBA WSPÓŁPRACUJĄCA PRZY PROWADZENIU DZIAŁALNOŚCI GOSPODARCZEJ W ŚWIETLE PRAWA SOCJALNEGO - Skąpski, Michał (Wydział Prawa i Administracji UAM, 2000)
Normative changes of essential character which have been introduced recently in the field of social insurance are also strictly related to the notion of a person assisting in economic activity. Respite o f the change of definition itself of such a person - its legal status has been maintained but it is much less favorable in comparison with the position of the employees in the domain of social insurance. Most important doubts arose around such a situation where - in conformity with normative definition - a person employed on a basis of employment contract is counted among the class of persons assisting in economic activity. Or, such a person - despite of the unquestionable fact of enjoying the status of employment - did not enjoy the same status in the field of social insurance. Such a factual state was maintained within the new insurance system. The Author analyses legal regulations in this juridical matter with reference to dispositions of particular laws since the sixties. He is also having recourse to respective decisions of the Supreme Court; some of his comments are critical. Finally the Author discusses the issues of retirement pensions and annuities, indemnities for an accident and other questions related to legal position of an employee, o f the family of an employee and o f persons assisting in economic activities who are relation to them.
A PERSON ASSISTING IN ECONOMIC ACTIVITY IN THE LIGHT OF SOCIAL LEGISLATION